INVESTIGATION ON ANTIMICROBIAL RESISTANCE RATES IN COMMENSAL ESCHERICHIA COLI ISOLATES FROM BROILERS ORIGINATING FROM BULGARIA (2020-2024) - Valentina Urumova; Radostina Stefanova; Dima Dobreva (Archives of Veterinary Medicine)
The aim of the present study was to investigate the prevalence of resistance to several groups of antibiotics among commensal Escherichia coli bacteria isolated from broilers in Bulgaria. Between March 2020 and September 2024, a total of 510 cloacal swab samples were obtained from broilers on two poultry farms, one located in central Bulgaria and the other in the northern region of the country. Of the collected samples, 90 were taken from one-day-old broilers, 140 from 14-day-old broilers, and 280 from broilers aged 28 to 30 days. The total number of Escherichia coli isolates was 479, 89 of which from one-day-old broilers, 126 from 14-day-old and 264 from 28-30-day-old broilers. In addition, 12 samples were obtained from poultry litter, from which 10 Escherichia coli strains were isolated. The highest rates of resistance among commensal Escherichia coli from day-old birds were observed against ampicillin (49.4%), tetracycline (43.8%), followed by amoxicillin/clavulanic acid (34.8%). The strains resistant to the third-generation cephalosporins cefotaxime and ceftazidime were 7.9% and 3.4% respectively. The most prevalent resistance phenotype among the strains included resistance to aminopenicillins and tetracycline (28.1%), with the tetA gene being the most frequently detected (7.8%). The highest resistance rates ​​were against ciprofloxacin (73.8%) in strains from 14-day-old broilers, while the highest resistance rate in isolates from 28-30-day-old birds was against ampicillin (65.6%). Tetracycline-resistant strains were 69.0% and 60.6%, respectively. The phenotypic profile including resistance to beta-lactams, tetracycline and ciprofloxacin predominated among 28.8% of the strains from both groups of broilers, with the highest prevalence for the tetA (26.4%) and qnrS (15.1%) genes. In the resistant strains isolated from poultry litter, the highest resistance rates were against ampicillin (100%), followed by tetracycline (80%), amoxicillin/clavulanic acid (70%) and ciprofloxacin (60%).